FeOx@GAC catalyzed microbubble ozonation coupled with biological process for industrial phenolic wastewater treatment: Catalytic performance, biological process screening and microbial characteristics. (15th February 2021) - Deng, Shihai; Jothinathan, Lakshmi; Cai, Qinqing; Li, Rui; Wu, Mengyuan; Ong, Say Leong; Hu, Jiangyong
Highlights: Microbubble ozonation (O3 ) and bioprocess were coupled for industrial PWW treatment. FeOx @GAC catalyzed O3 improved BOD5 /COD by 0.45 and reduced bio-toxicity by 79%. O3 /FeOx @GAC-MBR process achieved efficient COD (98%) and phenolics (99%) removal. The pretreatment of PWW by O3 /FeOx @GAC mitigated membrane fouling of MBR by 88%. Mycobacterium was abundant and proved antitoxic and capable of phenols degradation. Abstract: Phenolic compounds are common ccontaminants in industrial effluents. In this study, a combined catalytic microbubble ozonation and biological process was developed and applied for efficient industrial phenolic wastewater (PWW) treatment. Catalytic activity of an iron-oxides (FeOx ) doped granular activated carbon (GAC) catalyst (FeOx @GAC) in microbubble ozonation for PWW treatment was investigated. The results demonstrated that the FeOx @GAC catalyzed microbubble ozonation (O3 /FeOx @GAC) obtained significantly higher reaction rate constant (k1  = 0.023 min −1 ) in TOC removal compared to the bare GAC catalyzed microbubble ozonation (O3 /GAC, k1  = 0.013 min −1 ) and ordinary microbubble ozonation (k1  = 0.008 min −1 ). Destruction rate constant of phenolic compounds (k2 ) was improved from 0.014 min −1 (ordinary microbubble ozonation) to 0.025 min −1 (O3 /FeOx @GAC). The 60-min pretreatment of PWW by O3 /FeOx @GAC process enhanced BOD5 /COD ratio from 0.31 to 0.76 and reduced the acute bio-toxicity by 79.2%. Screening and characterization of biological post-treatment processes were conducted among activated sludge process (ASP), up-flow anaerobic sludge blanket (UASB) and membrane bioreactor (MBR). UASB and ASP showed limited phenolic compounds removal of 35.4% and 57.0% with lower bio-toxicity resistance than MBR (94.9% phenolic compounds removal). The combined process O3 /FeOx @GAC-MBR was thus developed and achieved high COD removal (98.0%) and phenolic compounds degradation (99.4%). PWW pretreatment by O3 /FeOx @GAC process decreased membrane fouling rate of MBR by 88.2% by reducing proteins/polysaccharides accumulation in both extracellular polymeric substances and soluble microbial products. 16S rRNA high-throughput sequencing revealed the predominance of phylum Proteobacteria, class Alphaproteobacteria and genera Mycobacterium, Gordonia, Pedomicrobium & Defluviimonas in biological PWW treatment bio-systems. Pearson correlation coefficient and ANOVA analysis verified that Mycobacterium possessed high bio-toxicity resistance and was the main contributor to the biodegradation of phenolic compounds. Graphical abstracts: Image, graphical abstract